Daily survival and dispersal of adult Rhagonycha fulva (Coleoptera: Cantharidae) in a wooded agricultural landscape - Laura E. RODWELL; Jennifer J. DAY; Christopher W. FOSTER; Graham J. HOLLOWAY (European Journal of Entomology, 2018)
Studies of insect population under field conditions to establish survival rates, longevity and dispersal rates are rare in the literature. These types of studies are important and can be used to inform studies of the effects of landscape composition and configuration on levels of biodiversity. Here the Cantharidae beetle, Rhagonycha fulva is studied under field conditions to derive estimates of daily survival rates for both males and females as well as local dispersal rates. Survival was studied at two sites, one in Wales and another in England, whilst dispersal was examined only at the Welsh site. Beetles were marked using different coloured enamel paints at the mid-point of a 200 m linear transect. The beetles were almost exclusively found (and marked) on common hogweed, Heracleum sphondylium. No difference in survival was found between males and females at both of the sites. The survival rates found at the two sites also did not differ. The overall daily survival rate was 0.771 equating with a median longevity of 4.37 days. Casual observations yielded a small number of marked individuals in excess of 400 m away from the point of marking. Movement of males along the transect differed from females. Marked females were never found far from the point of marking whilst males moved further away with time. This difference in behaviour is discussed in terms of hypothesized insect dispersal behaviour following emergence as mobile adults.